Spiral microstrip antenna - Kee, Sen Chee. (2009)
In this knowledge based era, people thirst for information on the move. This is made possible with cellular network, wireless network, Bluetooth, WiMAX etc. Antennas are an integral part of these networks. However, antennas are generally unable to support such a wide range of frequencies for use by the different technologies. Hence this project aims to design and fabricate a Frequency Independent Antenna, commonly in the form of a Spiral Antenna which has a wideband capability to achieve a single antenna for all common communication technologies in the frequency band from 0.6 GHz to 7GHz.